Konstruksi Sosial Stigma terhadap Penyandang Dwarfisme : Pelabelan, Stereotip, dan Eksklusi dalam Interaksi Sosial Masyarakat Pedesaan - Putri Rahma Dania Putri; Ali Akbarjono; Sepri Yunarman; Rossi Delta Fitrianah (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Abstract Individuals with dwarfism represent one of the most stigmatized yet least studied groups in Indonesian social science. Despite growing attention to disability and social exclusion, no prior study has examined how stigma is socially constructed and systematically reproduced within a homogeneous rural community in Indonesia. This study addresses that gap by analyzing the social construction of stigma against individuals with dwarfism in Palak Siring Village, Kedurang District, South Bengkulu Regency, with particular attention to the mechanisms of labeling, stereotyping, and social exclusion as theorized by Goffman (1963) and Link & Phelan, (2001). Using a qualitative descriptive approach with a single case study design, data were collected over one month (26 February– 26 March 2026) through in-depth interviews with five individuals with dwarfism, the village head, community members, and the parent of one participant, supplemented by participant observation and document analysis. Findings reveal that stigma is constructed and reproduced through five interrelated mechanisms: verbal stigma via normalized derogatory labeling; nonverbal stigma through excessive staring and patronizing attention; ability stereotyping that conflates physical difference with functional incapacity; indirect social discrimination through passive-only participation in community activities; and self-stigma resulting from the internalization of these cumulative stigmatic experiences. The study further identifies three distinct interaction patterns among participants, ranging from social withdrawal to selective and active engagement, shaped by individual resilience, personality, and family support. Efforts to reduce stigma remain informal, situational, and structurally unsupported. This study concludes that sustainable change requires a comprehensive approach that addresses not only individual attitudes but also the structural and cultural conditions that perpetuate stigma, including community education on dwarfism, strengthened village leadership, and the development of systematic inclusive social programs.